2022
DOI: 10.1038/s42255-022-00698-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of lipid metabolism modulation with fenofibrate for acute coronavirus disease 2019

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cytotoxicity may involve inhibition of peroxisome proliferator-activated receptor alpha. Fenofibrate activates peroxisome proliferator-activated receptor alpha and inhibits SARS-CoV-2 replication in vitro. Whether fenofibrate can be used to treat coronavirus disease 2019 (COVID-19) infection in humans remains unknown. Here, we randomly assigned inpatients and outpatients with COVID-19 within 14 d of symptom onset to 145 mg of oral fenofibrate nanocry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…The initial search with the keywords explained in supplementary table 1 resulted in 1,607 studies. Finally, after removing duplicates and screening by title and abstract and then full-text of studies, 10 articles remained to be included in our study [ 13 16 , 21 – 26 ]. A letter [ 27 ] was excluded from our systematic review due to the same population as the study by Pawelzik et al [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial search with the keywords explained in supplementary table 1 resulted in 1,607 studies. Finally, after removing duplicates and screening by title and abstract and then full-text of studies, 10 articles remained to be included in our study [ 13 16 , 21 – 26 ]. A letter [ 27 ] was excluded from our systematic review due to the same population as the study by Pawelzik et al [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The baseline features of the studies included in this review are shown in Table 1 . Atorvastatin was assessed in five trials [ 14 , 21 – 24 ], omega-3 in two [ 13 , 26 ], nicotinamide in one [ 15 ], fenofibrate in one [ 16 ], and PCSK9 inhibitors in one [ 25 ]. Most of the studies included hospitalized patients, except for Bikdeli et al [ 21 ] trial which was on COVID-19 cases admitted to ICU, Doaei et al [ 13 ] al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It attenuates the interaction between SARS-CoV-2 and ACE2, which could directly reduce infection-related inflammation. Unfortunately, an RCT has shown that fenofibrate has no effect on COVID-19 outcomes [ 153 ]. Pioglitazone and rosiglitazone are peroxisome proliferator activated receptor gamma (PPAR-γ,) agonists (thiazolidinediones) that also have anti-inflammatory activities in COVID-19 patients and have been suggested for treatment [ 154 , 155 ].…”
Section: Treating the Host Response With Inexpensive Generic Drugsmentioning
confidence: 99%